2020
DOI: 10.31234/osf.io/btmfy
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Efficacy of Attention Bias Modification Training for Depressed Adults: A Randomized Clinical Trial

Abstract: Background: This study examined the efficacy Attention Bias Modification Training (ABMT) for the treatment of depression. Methods: In this randomized clinical trial, 145 adults (77% female, 62% white) with at least moderate depression severity (i.e., self-reported Quick Inventory of Depressive Symptomatology (QIDS-SR) ≥ 13) and a negative attention bias were randomized to active ABMT, sham ABMT, or assessments only. Training consisted of two in-clinic and three (brief) at-home ABMT sessions per week for four w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 24 publications
2
10
0
Order By: Relevance
“…As previously reported (Hsu et al, 2021), intent-to-treat analyses of the time x group interaction indicated that active ABMT reduced depression symptom severity on the primary outcome, the QIDS-SR, to a greater extent than the other conditions. Compared to assessment only, depression was reduced by an additional 0.62 ± 0.23 (p = .008, d = -0.57) points per week.…”
Section: Overview Of Randomized Clinical Trial Procedures and Prior Findingssupporting
confidence: 78%
See 4 more Smart Citations
“…As previously reported (Hsu et al, 2021), intent-to-treat analyses of the time x group interaction indicated that active ABMT reduced depression symptom severity on the primary outcome, the QIDS-SR, to a greater extent than the other conditions. Compared to assessment only, depression was reduced by an additional 0.62 ± 0.23 (p = .008, d = -0.57) points per week.…”
Section: Overview Of Randomized Clinical Trial Procedures and Prior Findingssupporting
confidence: 78%
“…These group differences were maintained at a 3 month follow-up (Yang et al, 2015). A larger study (N = 145) compared the efficacy of active versus sham ABMT to an assessment only comparison condition among adults with depression and at least a moderate negative attentional bias (Hsu et al, 2021). In that study, active ABMT reduced gaze bias for sad stimuli and improved self-reported and interviewer-rated depression symptoms to a greater extent than assessment only (ds = -.57, -.49) and sham .…”
Section: Given This Correlational Evidence It Follows That Attention Bias Modificationmentioning
confidence: 97%
See 3 more Smart Citations